Modelo satelital para geração de chaves criptográficas perfeitamente seguras - Rodrigo dos Santos Marques Porto (2012)
This dissertation revisits the article Unconditional Security in Cryptography by Stefan Wolf [31], which addresses a model of key generation and key distribution that allows using a One-Time Pad with its characteristic security properties, something considered impossible for a long time. This model, based on a realistic scenario, uses the noise inherent to satellite communication in order to generate correlatedrandom strings which, after having been chosen appropriately to give advantage to the legitimate participants, are submitted to an error correction and privacy amplification phase. In this manner, the legitimate parties obtain a shared, highly secure, cryptographic key. This high level of security can be achieved even in the presence of an eavesdropper whose command of technology is superior compared to that of the legitimate participants, a property that is proven by using concepts fromInformation Theory.